Accession to the World Trade Organization as a factor changing the federal budget revenues of Russian Federation (Путеводитель предпринимателя, 2020)
The article presents a forecast o fchanges in the federal budget revenues of Russian Federation due to Russia’s entry to the World Trade Organization. The forecast is based on the economic development’s analysis of countries (who became WTO- members earlier than Russian Federation) right before and after accession to WTO.